Development of wireless sensor node for monitoring indoor air quality - Mahamad Noh, Norsyazila (2009)
This paper presents the application of Wireless Sensor Node in the Development of Wireless Sensor Node for Indoor Monitoring. Two major parameters qualify the indoor air quality except polluted gas, are air temperature and relative humidity. The LM35DZ temperature sensor and A0545 basic humidity sensor are used to measure air temperature and relative humidity in percentage. Functions of sensor node are transferring data from sensor to data handler. In this project, three sensor nodes are developed and each node consists of Microcontroller (PIC16F877), Transceiver and Sensor. This microcontroller programmed to read the temperature and relative humidity of workspace every hour for one day. For research and development purposes the system implemented at Research Assistance Laboratory (Sensor Node 1), Mechatronics and Consumer Laboratory (Sensor Node 2) and Advance Signal Processor Laboratory (Sensor Node 3), Faculty Electrical Engineering, MARA University of Technology Malaysia.